2022
DOI: 10.3390/biology11071061
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Physical Fitness and Health Evaluations for Police Officers: Brief Systematic Review with an Emphasis on the Portuguese Research

Abstract: This review aims (i) to identify and analyze the most used physical fitness tests for police officers (from international and Portuguese studies) and (ii) to understand the health-related physical fitness requirements according to the job descriptions of police officers. A total of 29 studies were included. Eighteen were from around the world and eleven were related to Portuguese police officers. All studies showed acceptable methodological quality in the assessment of physical fitness, and the most used fitne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…There is considerable scientific evidence that the PF of this TP is below the general population and health recommendations [ 5 , 6 , 7 ]. It has been extensively studied and shown that physical components such as cardiorespiratory fitness, muscular strength, and others are closely related to health parameters and improved quality of life and, consequently, enhanced job skills [ 8 , 9 , 10 ]. In accordance, a decline in exercise practice has implications for the health of TP, which ultimately impacts the organizations themselves (lower productivity levels [ 11 ]), given they are one of their greatest assets.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable scientific evidence that the PF of this TP is below the general population and health recommendations [ 5 , 6 , 7 ]. It has been extensively studied and shown that physical components such as cardiorespiratory fitness, muscular strength, and others are closely related to health parameters and improved quality of life and, consequently, enhanced job skills [ 8 , 9 , 10 ]. In accordance, a decline in exercise practice has implications for the health of TP, which ultimately impacts the organizations themselves (lower productivity levels [ 11 ]), given they are one of their greatest assets.…”
Section: Introductionmentioning
confidence: 99%
“…Also regarding age, Kukić et al [ 21 ] conducted a study with the aim of understanding whether there are significant differences in body composition between female POs of different ages, finding an increase in body mass index values, i.e., as people age, not only women but also men, tend to lose lean mass, resulting in a loss of strength, power, speed, flexibility, and cardiorespiratory capacity [ 25 ]. Given the indirect relationship that appears to exist between age and PF, POs must strive to maintain their level of PF as they age [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining physical fitness (PF) is essential to efficiently face the demands of this profession, as it is considered critical to adequately perform the activities associated with their role [ 1 ]. In this context, the literature highlights body composition, cardiorespiratory fitness, strength, muscular endurance, flexibility, agility, and speed as relevant attributes for the performance of the police profession [ 2 , 3 , 4 , 5 ], as well as a guarantee of health and well-being [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The protocol started with a 5 min warm-up at the maximal velocity reached on the shuttle run test. The shuttle run test has been selected as one of the most commonly used tests to assess cardiorespiratory capacity, as shown by Massuça et al [ 18 ]. The velocity was increased by 26.8 m/min every 2 min for 4 min, after which treadmill grade was increased by 2.5% every minute until volitional exhaustion.…”
Section: Methodsmentioning
confidence: 99%